Rancangan Kegiatan Literasi Informasi di SMA Negeri 1 Padang - Husna, Meisye Asmaul; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractBased on the results of research that has been done, the literacy activities at SMAN1 Padang are in accordance with the activities in the Master Design Movement of the School Literacy Movement, then it can be concluded as follows. First the design of information literacy activities at SMAN 1 Padang, namely: (1) reading activity 15 minutes before learning, i.e. making a literacy journal for students; (2) reading award, namely literacy ambassador. (3) Literacy corner, holding a reading corner in the park. (4) reading books by utilizing the role of the library, holding user guidance. (5) procurement of libraries as a source of literacy, making literacy bulletin boards. Second, constraints in the utilization of information literacy at SMAN 1 Padang, namely: limited implementation time in reading activities 15 minutes before learning, lack of placement of reading corners and completeness of reading collections in the literacy corner, lack of implementing reading award activities. Third, efforts to overcome obstacles in information literacy activities at SMAN 1 Padang, namely: increasing the implementation time of reading activities 15 minutes before learning, increasing collection and placement of reading corners in the school environment, continuing reading reading activities and adding prizes to students.Keywords: design, literacy